Issues in defining "Universal Social Work": Comparing Social Work in South Africa and Australia - Gray, A,F; Fook, J (Social Work/Maatskaplike Werk, 2002)
In this paper we discuss the issues involved in making generalisations about social work across different contexts by comparing the development of social welfare and the practice of social work in South Africa and Australia. Given that the idea of the profession is, to some extent, constructed in historical, social and cultural contexts, we next look at what this means for the idea of a universal definition of the social work profession and its implications for indigenous practice. We argue that while the discourse of social work might be similar across countries, the actual form and expression its practice takes may be quite variable. We end by appealing for a grounded approach where flexibility allows for relevant and appropriate practice responsive to local contexts yet still allows for accountability, connectivity and a common professional identity across countries in the belief that "because the form that social work takes is so intimately related to any society’s or country’s goals for itself and its people, its values, its mores, it is inevitable that forms of social work should differ from country to country, and that its patterns of social work education should differ from country to country" (Smalley, 1968: 163). Many social workers across the world are becoming more vocal about the forces of "professional imperialism", particularly in the developing world (Brigham, 1982; Campfen, 1988; Hammoud, 1988; Ife, 2000; Mandal, 1989; Midgley, 1981; Ow, 1991; Payne, 1997; Resnick, 1980; Rosenman, 1980; Tsang et al., 2000; Walton & Abo El Nasr, 1988). Over the past thirty years these social work writers have been trying to raise awareness of the dominance of Western influences on social work and have been stressing the need for social work in the developing world to free itself from the "in-built assumptions and cultural biases of first world theories and models of practice" (Cossom, 1990:3) and to develop indigenous education and practice (Brigham, 1982; Osei-Hwedie, 1995). Recognising the challenge to draw the best from international influences while developing local models of social work education and practice (Cossom, 1990), some have suggested social development as an alternative, as the case of South Africa will show (Gray, 1998; Midgley, 1995). Some writers question the universal applicability and superiority of professional social work values (Bar-On, 1998; Cossom, 1990; Tsang et al., 2000) while others draw attention to its unifying values, such as empowem1ent, justice, human rights, and equity (Hokenstad, Khinduka & Midgley, 1992; Ife, 2001). Still others caution against modification based approaches whereby social work development involves "adapting imported ideas to fit local needs" (Shawky, 1972:3). In Asia, as in Africa, discourse on the development of indigenous models tends to centre on the irrelevance and inapplicability of Western models (Midgley, 1981; Osei-Hwedie, 1995; Tsang et al., 2000). However, this is a contested domain. Hence lfe (2000: 150) warned against seeing Western social work as a "homogenous, monolithic entity’’ over which there was universal agreement. In the light of these broader debates, this paper explores the tensions between universalising forces in social work and indigenous practice. While we believe that there is room for many types of social work across widely divergent contexts, united by shared human rights and social justice goals, its mission may take various forms and expressions in different countries. We examine whether it is possible to develop local approaches to practice that are transferable across these diverse contexts. We argue that dialogical processes within local contexts are far more likely to create indigenous and relevant models of social work practice than imported ones, since they directly address the needs of the country, respond to the culture of the people and focus on pertinent social issues. This is not to say that there is not a shared area of understanding and that there are not commonalities in social work education, practice and research across the world. We believe it is important to facilitate discussion about the implications of internationalising trends in modem social work. We use Australia and South Africa, the contexts with which we are most familiar, in arguing for a "grounded approach" to exploring potential for shared models of practice.